Dynamics System in the SEIR-SI Model of the Spread of Malaria with Recurrence - Ahkrizal, Afdhal; Jaharuddin, Jaharuddin; Nugrahani, Endar H. (Jambura Journal of Biomathematics (JJBM), 2023)
Mathematical model is used to describe the dynamics of the spread of malaria in human and mosquito populations. The model used is the SEIR-SI model. This study discusses the stability of the equilibrium point, parameter sensitivity, and numerical simulation of the spread of malaria. The analysis shows that the model has two equilibrium points, namely the disease-free and endemic equilibrium points, each of which is locally asymptotically stable. Numerical simulations show that the occurrence of disease cure in exposed humans causes the rate of malaria spread to decrease. Meanwhile, the presence of disease recurrence causes the spread of malaria to increase.